2019
DOI: 10.26879/1007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the paleobiology of ammonoids (Cretaceous, Antarctica) using non-invasive imaging methods

Abstract: Based on medical computed tomography (CT) data, herein I document the ontogenetic changes in conch morphology of Maorites densicostatus and M. seymourianus. For this purpose, 20 specimens were measured in 30° steps starting from a shell diameter of 10 mm, to obtain the ontogenetic trajectories of several conch parameters. Results show that four morphological parameters, aperture height, whorl height, whorl width, and umbilical width have a low variation and can be easily modeled. In contrast, derived indices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the morphospace, these species share similar PC-scores for PC1, and most of the variation is explained by PC2 and PC3. An evolutionary tendency towards the more compressed form M. densicostatus was suggested in previous studies, but besides the increase in compression, no other evidence suggested an explanation to this speciation case (Macellari, 1986;Morón-Alfonso, 2019). Because PC2 and PC3 are related to the degree of compression and the shape of the ventral region, these PCs define the general outline of the conch and are likely important to determine its hydrodynamic performance.…”
Section: Biological Patternsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the morphospace, these species share similar PC-scores for PC1, and most of the variation is explained by PC2 and PC3. An evolutionary tendency towards the more compressed form M. densicostatus was suggested in previous studies, but besides the increase in compression, no other evidence suggested an explanation to this speciation case (Macellari, 1986;Morón-Alfonso, 2019). Because PC2 and PC3 are related to the degree of compression and the shape of the ventral region, these PCs define the general outline of the conch and are likely important to determine its hydrodynamic performance.…”
Section: Biological Patternsmentioning
confidence: 86%
“…A relevant case is observed in the Maorites species, M. densicostatus and M. seymourianus. These species share a very similar discoidal and subinvolute conch morphology (following Klug et al, 2015 terminology), and discrimination between both is based on the ornamentation and differences in the whorl width and whorl height in adults (see Morón-Alfonso, 2019). In the morphospace, these species share similar PC-scores for PC1, and most of the variation is explained by PC2 and PC3.…”
Section: Biological Patternsmentioning
confidence: 98%
“…Virtual models were constructed to determine the syn vivo hydrostatic properties of Nipponites mirabilis . Construction of the shell and other model components largely follow the methods of Peterman et al [ 37 – 39 ], although a CT scanned specimen was used as the base model instead of using photogrammetry (similar to the methods of Morón-Alfonso [ 51 ]). This modification from the previous methods was preferred for this species due to the complex changes in shell ornamentation (rib obliquity).…”
Section: Methodsmentioning
confidence: 99%
“…They also exhibit high intraspecific variation, possibly in response to variation in their environment [50][51][52][53] . As a result, the ontogenetic trajectory in morphological space of ammonoids is highly variable [54][55][56][57] . Taking these observations into consideration, it implies that the various patterns of conch morphology in ammonoids also differ from those in modern nautilids.…”
Section: Similarity Of the Three Morphological Parameters Among Taxa As Briefly Discussed In The Resultsmentioning
confidence: 99%